L’ACTE THÉRAPEUTIQUE ET LOGOTHÉRAPIE TRANS-NOÉTIQUE - KÜHN, Rolf (Studia Universitatis Babeș-Bolyai Philosophia, 2020)
The therapeutic act and trans-noetic logotherapy. This text shows the permanent interference of clinical and phenomenological data in the logotherapy of Viktor E. Frankl in what concerns the existential analysis from our historical being and its meaning. This debate remains essential for any reader and practitioner in current psychotherapy and psychoanalysis to identify the foundations of man in his trans-noetic unity of flesh, drive and spirit, engaging his freedom and responsibility from an original desire without particular object.